REEVALUASI IMPLEMENTASI UNDANG-UNDANG NARKOTIKA DI INDONESIA (STUDI HUKUM PERBANDINGAN) - DITA APRIANTI; M. AMIRUL AKBAR PRATAMA (GANEC SWARA, 2024)
This study examines the comparative policies on narcotics between Indonesia and the Netherlands using a qualitative approach with a legal comparative method. The primary data includes Indonesia’s Law No. 35 of 2009, supported by scientific literature, digital sources, and additional references. As a highly populated nation, Indonesia faces significant challenges related to narcotics abuse, which can negatively impact its economy and social stability. In tackling narcotics issues, Indonesia applies a repressive policy with severe penalties, contrasting with the Netherlands’ tolerance policy (gedoogbeleid), which distinguishes between hard drugs and soft drugs. This study identifies opportunities for Indonesia to adopt a more flexible approach, such as differentiating regulations by drug type and strengthening international collaboration. Additionally, improving rehabilitation services, public awareness campaigns, and technological applications in narcotics management are expected to effectively address this issue in Indonesia.